Investigating Host and Parasitic Plant Interaction by Tissue-Specific Gene Analyses on Tomato and Cuscuta campestris Interface at Three Haustorial Developmental Stages - Jhu, Min-Yao; Farhi, Moran; Wang, Li; Zumstein, Kristina; Sinha, Neelima R. (Frontiers in Plant Science, 2022)
Parasitic weeds cause billions of dollars in agricultural losses each year worldwide. Cuscuta campestris (C. campestris), one of the most widespread and destructive parasitic plants in the U.S., severely reduces yield in tomato plants. Reducing the spread of parasitic weeds requires understanding the interaction between parasites and hosts. Several studies have identified factors needed for parasitic plant germination and haustorium induction, and genes involved in host defense responses. However, knowledge of the mechanisms underlying the interactions between host and parasitic plants, specifically at the interface between the two organisms, is relatively limited. A detailed investigation of the crosstalk between the host and parasite at the tissue-specific level would enable development of effective parasite control strategies. To focus on the haustorial interface, we used laser-capture microdissection (LCM) with RNA-seq on early, intermediate and mature haustorial stages. In addition, the tomato host tissue that immediately surrounding haustoria was collected to obtain tissue- resolution RNA-Seq profiles for C. campestris and tomato at the parasitism interface. After conducting RNA-Seq analysis and constructing gene coexpression networks (GCNs), we identified CcHB7, CcPMEI, and CcERF1 as putative key regulators involved in C. campestris haustorium organogenesis, and three potential regulators, SlPR1, SlCuRe1-like, and SlNLR, in tomatoes that are involved in perceiving signals from the parasite. We used host-induced gene silencing (HIGS) transgenic tomatoes to knock-down the candidate genes in C. campestris and produced CRISPR transgenic tomatoes to knock out candidate genes in tomatoes. The interactions of C. campestris with these transgenic lines were tested and compared with that in wild-type tomatoes. The results of this study reveal the tissue-resolution gene regulatory mechanisms at the parasitic plant-host interface and provide the potential of developing a parasite-resistant system in tomatoes.